Audit Kepatuhan Sistem Informasi Akuntansi Investasi Pada Bisnis Rumah Kos Melalui Deteksi Pengendalian Internal - Feby Galih Saputra; Irma Nur Fadlia; Tri Ratnawati (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This article discusses the role of internal controls in investment accounting information systems for boarding houses and emphasizes the importance of compliance audits in detecting internal control weaknesses. The research aims to analyze the necessary internal controls, evaluate internal control weaknesses through compliance audits, investigate the effectiveness of internal controls, and provide benefits to boarding house owners and auditors. This study adopts a qualitative descriptive approach with a compliance audit method and a case study design. Data is collected through in-depth interviews and direct observations, and analyzed qualitatively using content analysis techniques. The findings of this research are expected to provide better insights into the required internal controls, identify internal control weaknesses, and offer recommendations to enhance the effectiveness of internal controls in investment accounting information systems for boarding houses.